A Case Report of Schizophrenia with Impaired Social Cognition - Faton Kutllovci; Nazmie F Ibishi; Afrim Ajradini; Ngadhnjim Rexhepi (International Journal of Biomedicine)
The cognitive impairment in schizophrenia involves social cognition as a core feature of the illness and one of the substantial implications for treatment and prognosis. In our case, the treatment of the schizophrenia patient was challenging to manage as the patient was continuously resistant to antipsychotic medications. As a result, social cognition was reduced: the patient could not work and had poor social performance and low emotional interactions with others. Cognitive behavioral and remediation therapy may be helpful in clinical settings to enhance the improvement of psychotic symptoms and social cognition.